2013
DOI: 10.1002/cbic.201300063
|View full text |Cite
|
Sign up to set email alerts
|

Configurational Assignment of Secondary Hydroxyl Groups and Methyl Branches in Polyketide Natural Products through Bioinformatic Analysis of the Ketoreductase Domain

Abstract: Profile hidden Markov models (HMMs) were used to predict the configuration of secondary alcohols and α-methyl branches of modular polyketides. Based on the configurations of two chiral centers in these polyketides, 78 ketoreductases were classified into four different types of polyketide producers. The identification of positions that discriminate between these protein families was followed by fitting six profile HMMs to the data set and the corresponding subsets, to model the conserved regions of the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 39 publications
0
34
0
6
Order By: Relevance
“…We therefore sourcedK Rd omains from modules of this type, ac hoice which additionally simplified the definition of the domain boundaries (the boundaries are shown in Figure S1 in the Supporting Information). We obtained and cloned 14 such epimerizing KR domains: [26] eight A2-type KRs (amphotericin (Amph) KR 1 and KR 11 , [27] concanamycin (Con) KR 4 and KR 10 , [28] elaiophylin (Ela) KR 4 , [29] oligomycin (Olm) KR 5 , [30] pimaricin (PIMS) KR 7 , [31] and candicidin (Can) KR 13 ) [32] and six B2-type KRs (erythromycin (DEBS) KR 1 , [33] lankamycin (Lkm) KR 1 , [34] pikromycin (Pik) KR 1 , [35] lasalocid (Las) KR 7 , [36] ECO-02301 (ECO) KR 19 , [37] and stambomycin (Sam) KR 21 ). [38] For KRs that are preceded by ar ecently identified dimerizationd omain, [39] the sequence encoding this region was also included, as done previously.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore sourcedK Rd omains from modules of this type, ac hoice which additionally simplified the definition of the domain boundaries (the boundaries are shown in Figure S1 in the Supporting Information). We obtained and cloned 14 such epimerizing KR domains: [26] eight A2-type KRs (amphotericin (Amph) KR 1 and KR 11 , [27] concanamycin (Con) KR 4 and KR 10 , [28] elaiophylin (Ela) KR 4 , [29] oligomycin (Olm) KR 5 , [30] pimaricin (PIMS) KR 7 , [31] and candicidin (Can) KR 13 ) [32] and six B2-type KRs (erythromycin (DEBS) KR 1 , [33] lankamycin (Lkm) KR 1 , [34] pikromycin (Pik) KR 1 , [35] lasalocid (Las) KR 7 , [36] ECO-02301 (ECO) KR 19 , [37] and stambomycin (Sam) KR 21 ). [38] For KRs that are preceded by ar ecently identified dimerizationd omain, [39] the sequence encoding this region was also included, as done previously.…”
Section: Resultsmentioning
confidence: 99%
“…To corroborate this assignment and to furnish the absolute configuration, we bioinformatically analyzed several of the ketoreductase (KR) domains. McDaniel and Caffrey previously determined key sequence signatures that separated KR domains into A- and B-type [78, 79], and this approach has been further expanded by more sophisticated methods including hidden Markov model (HMM)-based sequence classification [80]. This sequence-based approach has been used successfully to assign the absolute configuration of several polyketides and has been corroborated by analysis of the crystal structures of several representative KRs [14, 8183].…”
Section: Resultsmentioning
confidence: 99%
“…S9, Supplementary data). Kitsche and Kalesse demonstrated that KR sequence could also occasionally distinguish methyl stereochemistry [80]; indeed, using their HMM-based classification program ScoreDiff, KR9 is confidently predicted to give rise to an l α-methyl branch, although KR2, KR4, and KR5 methyl stereochemistry could not be reliably predicted using this method. The KR9 stereospecificity classification is especially important in the context of the spectroscopic ambiguity of the 8-C stereocenter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies würde nicht nur den Alkohol an C-27 erklären, fürd en das Vorhersageverfahren von Kitsche und Kalesse die richtige Ste-reochemie prognostiziert, [12] sondern auch die in Modul 4e rzeugte Doppelbindung. Dies würde nicht nur den Alkohol an C-27 erklären, fürd en das Vorhersageverfahren von Kitsche und Kalesse die richtige Ste-reochemie prognostiziert, [12] sondern auch die in Modul 4e rzeugte Doppelbindung.…”
Section: Angewandte Chemieunclassified